FRI0429 Hypocomplementaemia in A Cohort of Patients with Primary Sjogren's Syndrome (Gessar Registry). (10th June 2014) - Oliver, M.; Secco, A.; Gauna, M.; Puente, D.; Scarafia, S.; Carlevaris, L.; Bennasar, G.; Velez, S.; Zazetti, F.; Barreira, J.C.; Galván, L.; Caeiro, F.; et al.
Abstract : Background: the clinical significance of hypocomplementaemia in primary Söjgren Syndrome (SSp) is being studied due to recent studies that associated low complement levels with lymphoma development and mortality. Objectives: 1-To determine whether patients with SSp and hypocomplementaemia (C3 and/or C4) at diagnosis have an increased frequency of clinical manifestations (at least one of the following: parotid swelling, arthritis, Raynaud, purple, lung parenchymal involvement, renal impairment, neuropathy and lymphoma) compared with patients with normal complement. 2 - Assess differences between groups having each particular clinical manifestations, laboratory abnormalities and treatment with corticosteroids and immunosuppressants. Methods: We evaluated patients diagnosed SSp (all fulfilled the 2002 European American Criteria), using the GESSAR database of those patients with complement determinations at diagnosis. T test or Mann Whitney were used for the analysis of continuous variables and the categorical variables were analyzed by chi-square or Fisher exact test, as appropriate. Multivariate logistic regression analysis was performed. Results: 183 patients were taken randomly from 234 patients with complement determinations, 137 with normal complement and 46 with hypocomplementaemia (low C3 and C4 values in 22 patients, low C3 values in 4 and low C4 values in 20). 97.25% were females with a median age of 53.5 (IQR 43-63) and a median follow-up time for 3 years (IQR 1-5). The group with hypocomplementaemia showed a significant higher prevalence of clinical manifestations compared with patients with normal complement (71.74% versus 48.18%, p<0.01). When adjusting for FAN, anti Ro, anti- La and RF this association remained without seeing a confounding effect, or having observed a statistically significant association (OR: 2.73, 95% CI: 1.32-5.63, P<0.01). These manifestations were significantly associated with hypocomplementaemia: arthritis (44.19 vs 20.15%, p<0.01), purple (24.32 vs 5.3%, p<0.01), lung involvement (p<0.01 vs 21.74 6.57), neuropathy (22.22 vs. 9.09%, p: 0.03) and lymphoma (11.76 vs 0%, p=0.02). Conclusions: A higher frequency of extraglandular manifestations were found in patients with hypocomplementaemia, with a significant difference between patients with normal complement values. We emphasize that these findings should be considered while revealing the diagnosis of the disease and perform a close clinical follow-up due to the risk of having severe complications. References: M. Ramos-Casals et al. Hypocomplementaemia as an immunological marker of morbidity and mortality in patients with primary Sjögren's syndrome. Rheumatology 2005. Brito-Zerόn P et al. Predicting adverse outcomes in primary Sjögren's syndrome: identification of prognostic factors. Rheumatology 2007 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4511